Maintaining Quality Education at the University of Medan Area during COVID-19 Pandemic - Fauziah, Ida; Ramdan, Dadan; Karim, Abdul (Universitas Diponegoro, 2022)
Higher Education Institutions play a key role in achieving the 17 Sustainable Development Goals through teaching and learning, research as well as community services. COVID-19 Pandemic outbreak requires certain and special methods in conducting education systems especially in teaching and learning process as well as administrative affairs. Online system has become the most popular and preferable since March 2020 when lockdown enforcement was implemented at the University of Medan Area (UMA). It is much easier today at the UMA because an online system has been introduced for years before the outbreak. Besides applying numbers of online applications, UMA has also committed to align the curricula and research with Sustainable Development Goals.Keyword: Teaching and Learning, Program, SDGs, Pandemic